Optimizing Supply Chain Management with Real-Time Data Integration Platform - Lakshmi Bhargavi Mullapudi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Real-time data integration platforms have emerged as transformative solutions in modern supply chain management, revolutionizing how organizations process, analyze, and act on critical business information. These platforms enable seamless connectivity between suppliers, manufacturers, distributors, retailers, and customers, providing end-to-end visibility and enhanced decision-making capabilities. The evolution from traditional batch processing to real-time integration represents a fundamental shift in supply chain operations, addressing challenges such as data latency, system fragmentation, and operational inefficiencies. Through advanced technological components including sophisticated data ingestion layers, powerful processing engines, and efficient distribution systems, organizations can achieve substantial improvements in inventory management, order fulfillment, and customer satisfaction. The integration of artificial intelligence, edge computing, and blockchain technologies further enhances these capabilities, enabling predictive analytics, automated decision-making, and enhanced security measures. The implementation of these platforms, while challenging, offers significant strategic advantages including improved operational efficiency, reduced costs, and strengthened competitive positioning in the global marketplace.